VARIATIONS AND INSERTIONS OF SCHWA: EARLY TEENAGE L2 LEARNERS OF ENGLISH - Agor, John Tetteh (LLT Journal: A Journal on Language and Language Teaching, 2020)
This study examines variations and insertions of schwa observed in the speech of 200 early teenage pre-intermediate second-language learners of English. The respondents were final-year students of a junior high school located in an urban setting in Ghana, a multilingual post-colonial African country south of the Sahara. The respondents read aloud sections of familiar texts they themselves chose. The reading sessions and subsequent oral interaction sessions were video-taped, transcribed verbatim, and analysed. The respondents? articulation of schwa as captured in the recordings was compared with corresponding forms in the Ghanaian school variety of English. This variety served as the reference point for the comparisons made. Variations recognised were categorised and described focusing on their plausible sources. The findings indicate that all the unpredictable variants of schwa observed in their speech are traceable to their mother tongues. This has implications for second language theory, second language research, and second language pedagogy. DOI: doi.org/10.24071/llt.2020.230101